2(y+8)=3(y-2)

Simple and best practice solution for 2(y+8)=3(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y+8)=3(y-2) equation:


Simplifying
2(y + 8) = 3(y + -2)

Reorder the terms:
2(8 + y) = 3(y + -2)
(8 * 2 + y * 2) = 3(y + -2)
(16 + 2y) = 3(y + -2)

Reorder the terms:
16 + 2y = 3(-2 + y)
16 + 2y = (-2 * 3 + y * 3)
16 + 2y = (-6 + 3y)

Solving
16 + 2y = -6 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
16 + 2y + -3y = -6 + 3y + -3y

Combine like terms: 2y + -3y = -1y
16 + -1y = -6 + 3y + -3y

Combine like terms: 3y + -3y = 0
16 + -1y = -6 + 0
16 + -1y = -6

Add '-16' to each side of the equation.
16 + -16 + -1y = -6 + -16

Combine like terms: 16 + -16 = 0
0 + -1y = -6 + -16
-1y = -6 + -16

Combine like terms: -6 + -16 = -22
-1y = -22

Divide each side by '-1'.
y = 22

Simplifying
y = 22

See similar equations:

| A=b+8 | | 9x=22+7x | | -4x+24=-44 | | 4x-1=67+x | | 8-a-9=7a-6 | | -4x+24=-24 | | 7x-11=-67 | | 5-4x=-6x+5 | | 5z^3+15z^2= | | 6y^2-12y=gcf | | 2(x-5)-4=0 | | -6(x+1)-11=32+5 | | 9-2x=x-27 | | ln(x+11)-ln(x-3)=ln(3) | | 7(5c-1)-8=33c+7 | | 2x^4-4x^3-x^2+2x=gcf | | -24=21x | | -3x+5=-31-7x | | 3x+9=10y+8 | | 5z^3+15z^2+3z+9= | | 16x+4y=7 | | -56-2x=5x+7 | | 2x+-6+-4x+9=5x | | x(x+13)=x+10(x+1) | | y/5-9=-2 | | 6=12s-6/5 | | 1=.5x-1 | | 2x-6-4x+9=5 | | w/2+14=12 | | x-1/2=5/6 | | 5y+26=y+10 | | (v^2-3v-40)/(v+3) |

Equations solver categories